Outcomes of transurethral resection of the prostate for benign enlargement of prostate in patients with and without retention of urine - Khanal, Sandeep; Shah, Raaii; Shah, JN; Chudal, Sampanna; Khadka, Dipesh; Adhikari, Kapil (Journal of Chitwan Medical College, 2025)
Introduction: Benign enlargement of the prostate (BEP) is a common condition in aging males, often leading to urinary symptoms. Transurethral resection of the prostate (TURP) is gold standard, but postoperative complications vary among patients with and without history of urinary retention. The aim of the study was to evaluate outcomes after TURP in BEP patients who presented with or without retention before surgery. Method: A retrospective study was conducted with inclusion of all patients who underwent TURP for BEP for 3 years from 2020 and 2023. The study was approved from the ethical committee. The study compared the clinical outcomes of TURP in patients with and without a history of urinary retention, focusing on complications such as re-catheterization rates, haematuria, fever, and length of hospital stay. The SPSS was used for data analysis. A X2 test was used find out the association. A p<0.05 was considered statistically significant. Result: Out of 183 patients, 42(22.9%) had history of urinary retention (Gr-1) and 141(77.1%) no retention (Gr-2). Patients in Gr-1 were older (73.5 vs. 69.4 years), had higher BMI (26.1 vs. 23.4, p=0.0025) and higher re-catheterization (23.8% vs. 0.7%, p=0.002). Haematuria (33.3% vs. 2.1%, p=0.108) and fever was (4.8%) was more frequent in Gr-1. Length of hospital stay in Gr-1 was shorter (5 vs 6 days, p=0.01) as the re-catharized patients were discharged with catheter on the same day. Conclusion: Patients with preoperative urinary retention undergoing TURP are at a higher risk of re-catheterization, along with hematuria and fever.